Exploring EFL Pre-Service Teachers' Attitudes Toward KWL To Enhance Reading Comprehension: A Multi-Case Study - Yasin, Muhammad Ilham; Dwiananto, Gigih; Prasetiyo, M. Teguh (LP3M Universitas Islam Zainul Hasan Genggong, 2022)
This study investigates the attitudes of English as a Foreign Language (EFL) pre-service teachers toward the use of the KWL (Know-Want to know-Learned) strategy to enhance reading comprehension skills. The KWL strategy, a three-step framework designed to activate prior knowledge, set learning objectives, and reinforce retention, is commonly used to improve reading comprehension. Through a multi-case study approach, this research gathers data from interviews, classroom observations, and reflective journals to analyze pre-service teachers' perceptions of KWL’s effectiveness in diverse classroom contexts. Findings reveal that pre-service teachers view KWL as a valuable instructional tool that engages students actively and facilitates deeper understanding of texts. However, some challenges in implementation are noted, particularly regarding adapting KWL to varied reading levels and managing class time effectively. This study provides insights into the benefits and limitations of KWL as perceived by pre-service teachers, contributing to the development of effective reading instruction practices in EFL settings.